Higher risk for poor handwriting in Taiwanese children born late preterm - Yea-Shwu Hwang; Chih-Cheng Chen; Hui-Ning Shih; Wen-Hui Tsai (Pediatrics and Neonatology)
Background: Late-preterm and early-term births constitute a significant proportion of live births. However, handwriting skills of these two populations remain unclear. We aimed to investigate their risk for poor Chinese handwriting in grade two. Methods: In this observational study, 185 second graders born late preterm (34+0–36+6 weeks' gestation, n = 54), early term (37+0–38+6 weeks' gestation, n = 56), and full term (39+0–41+6 weeks’ gestation, n = 75) without any intervention or diagnosis related to developmental delays were included. Their handwriting performance was rated by class teachers using the Chinese Handwriting Evaluation Form (CHEF), which is a standardized handwriting scale including five handwriting dimensions (construction, accuracy, directionality, speed, and pencil grasp). Results: After controlling for demographic risk factors, the late-preterm born group had a greater risk of having worse performance in the full form (adjusted odds ratio [aOR] = 3.93; p = .038) and construction dimension (aOR = 4.77; p = .009) of the CHEF than peers born at full term, whereas the risks were comparable for the early- and full-term born groups (aOR = 0.14–1.90; p = .073–0.453 in the handwriting dimensions). Conclusions: Late-preterm but not early-term born children were found to be at higher risk for poor Chinese handwriting in grade two. They particularly have difficulty with spatial construction including size, spacing, and alignment of Chinese characters and components that may influence handwriting legibility.